Imbibing Industry Requirements in Engineering Curriculum by Augmenting it with Industry Standard Simulation Tool - Itagi, Anupama R.; Sushma, V. (Journal of Engineering Education Transformations, 2017)
At the end of graduation, young engineers will be acquainted with rich theoretical background. However students lack applying this knowledge in real time. Hence darning of curriculum is required to meet at least few employer requirements. This can be done by industry- academia interaction. Considering the input of experts, course instructor should follow a well-focused and designed pedagogical method to train students. In this paper authors discuss about effective Teaching-Learning process for undergraduate students with an aid of Industry Standard simulation tool. It is proposed to use Industry Standard simulation tool PSpice for various mandatory courses like Circuit Analysis (CA),Analog Electronic Circuits (AEC), Digital Electronics Circuits (DEC). This helps in making students meet the preliminary step in the design of Embedded Systems.Typical PSpice simulation examples on each course mentioned above are included and possible outcomes and achievement of Performance indicators are also discussed.